Critical Thinking Skills / Developing Effective Analysis and Argument - Cottrell Stella (Palgrave Macmillan, 2005)
This book takes an easy-to-follow, step-by-step approach to developing a range of critical thinking skills, with clear explanations, good examples and plenty of activities to develop your understanding at each level. Introduction, Glossary, Acknowledgements, What is Critical Thinking?, How Well Do you Think? Develop Your Thinking Skills, What's Their Point? Identifying Arguments, Is It an Argument? Argument and Non-Argument, How Well Do They Say It? Clarity and Consistency and Structure, Reading Between the Lines: Recognizing Underlying Assumptions and Implicit Arguments, Does It Add Up? Identifying Flaws in the Argument, Where's the Proof? Finding and Evaluating Sources of Evidence, Critical Reading and Note-Making: Critical Selection and Interpretation and Noting of Source Material, Critical and Analytical Writing: Critical Thinking When Writing, Where's the Analysis? Evaluating Critical Thinking, Appendix, Bibliography, Index.